2019
DOI: 10.1155/2019/5320902
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of VEGF and PEDF in Placentas of Women with Lower Extremity Venous Insufficiency during Pregnancy and Its Implication in Villous Calcification

Abstract: Pregnancy is a period in a woman's life in which changes can occur that affect different physiological processes. Common conditions during this period include vascular changes, such as lower extremity venous insufficiency (VI). This is an observational, analytical, and prospective cohort study in which 114 pregnant women were analyzed, of which 62 were clinically diagnosed with VI. In parallel, 52 control patients without VI (HC) were studied. The aim of this study was to observe changes in angiogenesis and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…Several pathogenic mechanisms that affect the placenta in this disease have been described such as cell hypoxia, oxidative stress, extracellular matrix remodeling, and angiogenesis/lymphogenesis [12]. While CVD is a less serious condition, in prior work we also detected these changes in the placentas of women with venous insufficiency, indicating the possible impact of venous disease in these patients with CVD [9,[13][14][15]. Chronic venous insufficiency has also been associated with a series of changes in cell signaling and in the behavior of smooth muscle cells.…”
Section: Ivyspring International Publishersupporting
confidence: 52%
“…Several pathogenic mechanisms that affect the placenta in this disease have been described such as cell hypoxia, oxidative stress, extracellular matrix remodeling, and angiogenesis/lymphogenesis [12]. While CVD is a less serious condition, in prior work we also detected these changes in the placentas of women with venous insufficiency, indicating the possible impact of venous disease in these patients with CVD [9,[13][14][15]. Chronic venous insufficiency has also been associated with a series of changes in cell signaling and in the behavior of smooth muscle cells.…”
Section: Ivyspring International Publishersupporting
confidence: 52%
“…Pregnancy causes haemodynamic and mechanical changes, triggering vascular complications such as lower extremity CVD [23]. Our previous studies showed how impaired venous hypertension and venous return resulting from CVD during pregnancy created an environment of cellular hypoxia with associated cell damage, producing extracellular matrix remodelling [10][11][12]. In the present study, we saw an increase in the proangiogenic and lymphangiogenic markers CD31, D2-40, Flt-1, and PIGF in placental villi of women with CVD during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…We also saw this abnormal profile of Flt-1 and PIGF in placental villi, both of which were upregulated in the extracellular matrix. Placental villi of women with CVD have shown an increased expression of VEGF [12], explaining how vascular compromise resulting from CVD during pregnancy induces angiogenesis and lymphangiogenesis in placental villi. The placentas of our women with CVD had more villi with PAS-positive material than the control placentas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations